2019
DOI: 10.1136/bmjopen-2018-026581
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association between migraine and fibromyalgia: retrospective cohort analyses of two populations

Abstract: ObjectiveFibromyalgia (FM) and migraine are common pain disorders that tend to coexist. This study determined whether these two conditions exhibited any mutual influences.SettingCohort study.ParticipantsA retrospective, longitudinal cohort study was conducted using data obtained from a nationwide healthcare database. This study had two arms. Arm 1 comprised 33 216 patients with FM and arm 2 consisted of 7420 patients with migraine; all of these patients were diagnosed between 2000 and 2010. Using the aforement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 50 publications
2
32
0
Order By: Relevance
“…However, we found no significant association between fibromyalgia and migraine or neuropathic pain. These results rather contradicted findings in the literature [34][35][36]. Akdag Uzun et al concluded that fibromyalgia occurred with greater frequency in patients with migraine, which supported a hypothesis that dopamine might play a role [37].…”
Section: Discussionmentioning
confidence: 87%
“…However, we found no significant association between fibromyalgia and migraine or neuropathic pain. These results rather contradicted findings in the literature [34][35][36]. Akdag Uzun et al concluded that fibromyalgia occurred with greater frequency in patients with migraine, which supported a hypothesis that dopamine might play a role [37].…”
Section: Discussionmentioning
confidence: 87%
“…Several studies have reported a high prevalence (up to 80%) of FM in patients with CM (9,10,13,14), and there is a large body of evidence that central sensitization comprises the common pathophysiologic basis (1). FM and migraine when present together contribute to increased disability.…”
Section: Discussionmentioning
confidence: 99%
“…CM is a prevalent and disabling neurologic disorder that is often associated with comorbid conditions that can influence both its prognosis and its impact on quality of life ( 1 , 3 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Norepinephrine and serotonin inhibit central excitability, but low norepinephrine and serotonin levels were noted in patients with depression. Serotonin deficiency increases painful sensation in chronic pain [ 26 ], and low norepinephrine was noted in migraine [ 27 ]. Migraine with psychological syndrome increases symptom severity and requires hospital treatment.…”
Section: Discussionmentioning
confidence: 99%